2020
DOI: 10.15294/eej.v10i1.33994
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Functions of Lexical Bundles in Findings and Discussion Sections of Graduate Students’ Thesis

Abstract: Lexical bundles is a combination of words which consists of three or even more words that frequently occur together in particular registers. It is seen as an important aspect that should be mastered in order to create a qualified text. This study aims at analyzing the lexical bundles used in findings and discussion sections of graduate students’ thesis in terms of structures, functions, and the role of lexical bundles in forming coherence of the students’ texts. This study emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Together they accounted for over half of the extracted bundles in MRA abstracts of foreign and Iranian journals. In terms of the functional patterns, consistent with the results of the previous researchers (e.g., Hyland, 2008a;Rezoug & Vincent, 2018;Wachidah, Fitriati, & Widhiyanto, 2020), research-oriented bundles were predominant in MRA abstracts of both classes. However, as clearly illustrated, significant differences were seen in the distribution of sub-structures, sub-functions, and frequencies of the shared bundles in MRA abstracts of foreign and Iranian journals.…”
Section: Discussionsupporting
confidence: 91%
“…Together they accounted for over half of the extracted bundles in MRA abstracts of foreign and Iranian journals. In terms of the functional patterns, consistent with the results of the previous researchers (e.g., Hyland, 2008a;Rezoug & Vincent, 2018;Wachidah, Fitriati, & Widhiyanto, 2020), research-oriented bundles were predominant in MRA abstracts of both classes. However, as clearly illustrated, significant differences were seen in the distribution of sub-structures, sub-functions, and frequencies of the shared bundles in MRA abstracts of foreign and Iranian journals.…”
Section: Discussionsupporting
confidence: 91%
“…The mean score of pretest of the experimental group is 51.72, while the control group is 68.28. (2017_TR) However, the findings of this research were different from the previous study by Wachidah et al (2020) who identified other prepositional phrase fragments (following Biber"s taxonomy) such as "from the result of", "in the same time", and "by looking at the" as the most frequent lexical bundles in ten Findings and Discussion section of graduate students theses. Previous research which used a manual approach to identify lexical bundles in ten graduate students" theses might account for the differences.…”
Section: Structural Types Of Lexical Bundlescontrasting
confidence: 99%
“…They found that research-oriented bundles dominated the text. In addition, Wachidah et al (2020) found that text-oriented was the most frequent lexical bundles in Findings and Discussion section of ten graduate students theses.…”
Section: Lexical Bundlesmentioning
confidence: 95%
See 2 more Smart Citations